Determination of a factor VIII-interactive region within plasmin responsible for plasmin-catalysed activation and inactivation of factor VIII(a) - Nishiya, Katsumi; Nogami, Keiji; Okada, Kiyotaka; Matsuo, Osamu; Takeyama, Masahiro; Ogiwara, Kenichi; Shima, Midori (Thrombosis and Haemostasis, 2010)
Plasmin, an active form of plasminogen, activates and inactivates factor VIII (FVIII) by limited proteolysis. We have previously identifiedly sine-binding site-independent plasmin-interactive sites on the FVIII A2 domain responsible for cleavages at Arg336 and Arg372, together with lysine-binding site-dependent plasmin sites on the light chain responsible for cleavage at Lys36. We have now characterised FVIII-interactive regions on plasmin. SDS-PAGE analysis demonstrated that a monoclon al antibody (mAb) against kringle (K)5-catalytic domain (K5-CD) of plasmin significantly blocked plasmin-catalysed cleavages at Arg336 and Arg372. K5-CD fragment and this mAb blocked plasmincatalysed activation and inactivation of FVIII(a). Anti-K1–2–3 and anti-K4 mAbs blocked plasmin-catalysed cleavages at Lys36, and K1–2–3 and K4 fragments inhibited plasmin-catalysed inactivation of A11–336 FVIIIa. The K5-CD preferentially bound to the A2 domain (Kdapp ; 52 nM), whilst the K1–2–3 and K4 bound to the light chain (Kdapp; 75 and 106 nM, respectively) in ELISA. Binding was attributed to the A2 484–509 region and A3 1690–1705/1804–1818 region, respectively. 6-aminohexanoic acid, a lysine analogue, significantly inhibited the light chain/K1–2–3 (and K4) binding by ∼90%, whilst A2/K5-CD binding was moderated by only ∼35%. Furthermore, an anti-CD antibody blocked plasmin-catalysed cleavage by inhibiting the A2/K5-CD interaction. These data demon strate that the K5-CD of plasmin (and plasminogen) interacts with the A2 domain independent of lysine-binding site, whilst interactions of K1–2–3 and K4 with the light chain are lysine-binding site-dependent. Interactions between the K5-CD and A2 likely constitute the major regulatory mechanism for activation and inactivation of FVIII(a) mediated by cleavage at Arg372 and Arg336.
Keywords: Activation/inactivation; binding-site; factor VIII(a); kringle domain; plasmin(ogen)